The Indonesian version of the Early Childhood Screening Assessment (ECSA_INA) to screen for social, emotional and behavioral disorders in children - Rosana, Elvira; Anggraini, Alifah; Sitaresmi, Mei Neni (Paediatrica Indonesiana, 2025)
Background  The incidence of emotional, social, and behavioral disorders in children is quite high in the world, including in Indonesia. Therefore, earlier screening is necessary for effective treatment. Currently there is no screening tool for emotional, social, and behavioral disorders in children, especially toddlers, that has been validated in Indonesia. The Early Childhood Screening Assessment (ECSA) is a widely used and recommended instrument for children aged 1.5 - 5 years. This research aims to carry out a cross-cultural adaptation of ECSA in Indonesian (ECSA_INA) and assess its internal validity and reliability. Methods The study consisted of 2 phases: transcultural adaptation and internal validity and reliability testing on parents of children aged 1.5-5 years The first phase consists of the forward translation of original instruments into Indonesian, synthesis from experts and backward translation to the original language and then discussion by experts. Furthermore, pre-testing was carried out in 6 parents of children aged 1.5-5 years. We conducted the second phase of the internal validity and reliability test on 70 parents of children aged 1.5 - 5 years. Each respondent filled in ECSA_INA 2 times, with an interval of 14 days. Furthermore, the data were analyzed statistically with the correlation test of Cronbach’s α, Intraclass Correlation Coefficient (ICC) and Pearson correlation. Results The internal consistency was good (Cronbach’s α = 0.831). Test- retest reliability was good with intraclass correlation coefficient (ICC) of 0.867 (p<0.000). Overall internal validity is good. Conclusion The ECSA_INA is a reliable and valid instrument for screening social, emotional and behavior in Indonesian children.